Academic buoyancy among female students of Umm Al-Qura University, Al-Zahir Branch - Qasim, Tahany Amaanullah (Journal of Educational and Psychological Sciences, 2023)
This research aims to determine the level of academic buoyancy among female students of Umm Al-Qura University in Makkah Al-Mukarramah and to reveal significant differences in academic buoyancy due to academic disciplines and academic year. The research instrument was applied to a sample consistes of (507) female students. Results of the research indicate that the level of academic buoyancy was high for the scale in general and for "coping with difficult situations" dimension, while it was medium for "resisting pressure" and "social support" dimensions. In addition, the differences in academic buoyancy were significantly higher for students in theoretical disciplines than science disciplines, while the differences due to academic year were not.